Handbook of CH-Functionalization 2022
DOI: 10.1002/9783527834242.chf0100
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed C(sp 2 )H Functionalization under Au(I)/Au(III) Catalysis

Abstract: Among the newer approaches to transition metal‐catalyzed CH functionalization, Au(I)/Au(III) catalysis has emerged as a powerful synthetic tool for the construction of carbon–carbon and carbon–heteroatom bonds. The orthogonal reactivity pattern of gold catalysts as compared to other transition metal catalysts provides an excellent opportunity for the development of new modes of CH functionalization. The rapid enhancement in the field of gold‐catalyzed CH functionalization is complemented by the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Ironically, recent research revealed that gold can act as an efficient catalyst. 5 Due to the relativistic effect, 6 gold complexes have emerged as excellent soft π-Lewis acid catalysts in numerous homogeneous transformations. 7 In general, these reactions involve the activation of C–C multiple bonds towards intra- or intermolecular nucleophilic attack followed by protodeauration to provide new C–C or C–X bonds.…”
Section: Multicomponent Reactions – An Overviewmentioning
confidence: 99%
“…Ironically, recent research revealed that gold can act as an efficient catalyst. 5 Due to the relativistic effect, 6 gold complexes have emerged as excellent soft π-Lewis acid catalysts in numerous homogeneous transformations. 7 In general, these reactions involve the activation of C–C multiple bonds towards intra- or intermolecular nucleophilic attack followed by protodeauration to provide new C–C or C–X bonds.…”
Section: Multicomponent Reactions – An Overviewmentioning
confidence: 99%
“…23 Notably, despite such significant developments, there exist no report on 1,2-dicarbofunctionalization of alkynes using organohalides. 24 This could be attributed to various challenges like facile Au(I)- 13,25 and Ag-catalyzed 26 hydroarylation, stable vinyl-Au(I) species formation, direct cross-coupling 27 and regioselectivity issues. Notably, the successful implementation of this reaction paradigm could act as an important step towards the development various gold-catalyzed 1,2-difunctionalization reactions of alkynes using organohalides.…”
Section: Scheme 1 Background and Synopsis Of Current Workmentioning
confidence: 99%
“…Zhou and co-workers, in 2016, developed a sequential process consisting of Au( i )-catalyzed C–H functionlizaton 27 and a chiral tertiary amine-catalyzed Michael addition reaction (Scheme 9a). 28 In the presence of 1.5 mol% Ph 3 PAuOTf, 29 diazooxindole 9a undergoes C–H insertion with the aromatic compounds 9b to form 3-aryloxindoles 9c .…”
Section: General Introductionmentioning
confidence: 99%